2013
DOI: 10.1371/journal.pone.0063405
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Histone Acetylation Facilitates Hepatic Differentiation of Human Bone Marrow Mesenchymal Stem Cells

Abstract: The multi-potentiality of mesenchymal stem cells makes them excellent options for future tissue engineering and clinical therapy, including liver injury. In this study, we investigated the effects of valproic acid (VPA), a direct inhibitor of histone deacetylase (HDAC), on the hepatic differentiation of human bone marrow mesenchymal stem cells (BMMSCs). The cells were found to differentiate into a more homogeneous hepatocyte-like population when pretreated with 5 mM VPA for 72 h. The expression of liver-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 22 publications
(22 reference statements)
6
33
0
Order By: Relevance
“…Our study, in serological functional assay, was proved the hEnSCs‐derived hepatocyte‐like cells synthesized both alpha‐fetoprotein and albumin. In a similar manner, some researchers were achieved functional hepatocyte derived from adult stem cells using sequential treatment with factors (Dong et al, ; Kazemnejad et al, ; Hashemi et al, ; No et al, ). These differentiated cells had hepatocyte cells feature comprising alpha‐fetoprotein, albumin, urea secretion, glycogen storage, indocyanine green uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Our study, in serological functional assay, was proved the hEnSCs‐derived hepatocyte‐like cells synthesized both alpha‐fetoprotein and albumin. In a similar manner, some researchers were achieved functional hepatocyte derived from adult stem cells using sequential treatment with factors (Dong et al, ; Kazemnejad et al, ; Hashemi et al, ; No et al, ). These differentiated cells had hepatocyte cells feature comprising alpha‐fetoprotein, albumin, urea secretion, glycogen storage, indocyanine green uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Bar 25 lm (Color figure online) apoptosis of tumor cells, increases cancer cell immunogenicity and inhibits angiogenesis and metastasis [43]. An increasing body of study demonstrates that VPA facilitates stem cell differentiation, such as hematopoietic stem cells [44], bone marrow-derived MSCs [45] and ESCs [46]. Abematsu et al [47] reported that VPA treatment promoted the differentiation of transplanted NSCs into neurons rather than glial cells in SCI.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro differentiation is usually obtained by the use of growth factors, especially Hepatocyte Growth Factor (HGF), although quite a number of differences exist between protocols [19,[23][24][25]. Some authors have shown differentiation also with hepatocyte conditionedmedium [21] or serum from patients with hepatitis B virus-associated liver cirrhosis [35], co-culture with hepatocytes [36][37][38] or liver fragments [39] from healthy or injured animals.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, BMMC are characterized by their ability to differentiate into several functional mature cell types both in vivo and in vitro, including cardiomyocytes [7,8], endothelial cells [9], neurons [10,11] and hepatocytes [12][13][14][15][16][17][18]. In addition, many groups have developed protocols for the in vitro differentiation of bone marrow-derived cells into hepatocyte-like cells [19][20][21][22][23][24]. Although bone marrow mononuclear fraction is used for in vivo transplantation, in vitro protocols usually work with Mesenchymal Stem Cells (MSC) [19,[23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation